Central control of local resource management: the impacts of devolution - Wollenberg, Eva Karoline; Campbell, Bruce M.; Shackleton, S.; Edmunds, D.; Shanley, P. (2003)
This paper evaluates the impacts of natural resource devolution policies in several Asian and southern African countries from the perspective of local people. Devolution outcomes are assessed in terms of who has greater benefits and decision-making authority. We also examine the factors that have influenced the devolution process. We conclude that: Most devolved NRM reflects some continuation of central government control and management over natural resources rather than a genuine shift in authority to local people. The ways in which local people realise the benefits of devolution differ widely and negative trade-offs, most felt by the poor, are common. States, communities and other stakeholders have different visions of devolution and its mode of implementation. A shared framework, more accountable to local livelihood needs and people’s rights to self-determination, is required. Redefining issues of wider ‘public interest’ forms part of this process. Organisational models that devolve authority directly to disadvantaged resource users are more embracing of local interests and priorities than those that allocate control to higher levels of social organisation. More powerful actors in communities tend to manipulate devolution outcomes to suit themselves. Checks and balances need to be in place to ensure that benefits and decision-making do not become controlled by elites. Strong local organisational capacity and political capital enhance outcomes for local people by enabling them to mobilize resources and negotiate for better benefits. NGOs, donors, federations and other external actors have a key role in moving devolution policy and practice towards local interests.